Terapi Fobia Matematika Menggunakan Multimedia “Digimonica” di SMA Islam Hasyim Asy’ari Batu - Ainur Rosikin; Yoga Klody Arianto; Nanda Amaliah Pramawanda; Abdul Halim Fathani (Jurnal Tadris Matematika, 2020)
The purpose of this study is to help students who experience mathematical phobia by conducting mathematical therapy. Mathematical therapy was carried out using multimedia "digimonica". This research used quantitative research methods, type of action research. The data sources in this study were 13 students of Class XI of SMA Islam Hasyim Asy'ari Batu who have a mathematical phobia. Data collection method was done by using tests and interviews. The action research process began with the identification of problems, namely the level of students' mathematical phobias. This process was carried out by conducting a pretest, then the researcher conducted a mathematical therapy action with multimedia "digimonica" as an effort to overcome the students' mathematical phobia, then ended with a posttest. Based on the results of the pretest and posttest, the data obtained changes in the level of mathematical phobia of students. In the initial conditions, there were three categories of students who had mathematical phobias (mild, moderate, high), whereas after mathematical therapy, the level of mathematical phobia decreased (mild and moderate). In general, the average student successfully answered more than 2 questions correctly. This proves that therapy using multimedia "digimonica" can help students to reduce the level of mathematical phobia.